Analisis Manajemen PAUD Berbasis Standar Akreditasi PAUD dan PNF di Kutai Kartanegara - Asiah, Siti Nor (SYAMIL: Jurnal Pendidikan Agama Islam (Journal of Islamic Education), 2018)
Achieving the objectives of Early Childhood Education is needed by an institution that deserves good quality and educational services. Then a quality assessment is needed in the feasibility of conducting education in an education unit called accreditation. The aim of the study was to describe PAUD management based on the National Accreditation Agency Standards in Kutai Kartanegara (Standard Levels of Achievement of Development, Content Standards and Process Standards). The methodology of this research uses qualitative research methods based on postpositivism philosophy or interpretive, naturalistic qualitative research methods whose processes are inductive, the data obtained are qualitative data, which will later be interpreted so that the meaning is understood. Data collection techniques are interviews, observation and documentation. The results showed that Mutiara Bunda Kindergarten was considered very Complete for Standard-based administration of the National Accreditation Agency, from 3 (three) standards, namely Standards for Achieving Child Development, Content and Process Standards, almost all documents owned. From the results of this study Mutiara Bunda Kindergarten has run its management management based on PAUD and PNF National Accreditation Standards as it should, from the 3 (three) standards it can be proved the administrative completeness of Mutiara Bunda Kindergarten so that it deserves A level of accreditation given by PAUD and PNF National Accreditation Agency in 2016. It is appropriate for the administration of documents from planning, implementation to evaluation to be carried out continuously not only at any time so that all management of the institution can be carried out professionally with the achievement of the level of development of students who are very good.